TEACHING READING HORTATORY EXPOSITION TEXT BY USING GIVE ONE, GET ONE STRATEGY TO THE ELEVENTH GRADE STUDENTS OF SMAN 7 PALEMBANG - Zuria Kausari (Pusat Studi Pendidikan Bahasa Inggris Fakultas Ilmu Tarbiyah dan Keguruan Universitas Negeri Raden Fatah Palembang, 2016)
The objectives of this study are to find out whether or not there is a significant improvement before and after the treatment on the eleventh grade students' reading comprehension scores of SMAN 7 Palembang by using Give One, Get One strategy and to find out whether or not there is a significant difference on the eleventh grade students' reading comprehension scores of SMAN 7 Palembang between the students who are taught by using Give One, Get One strategy and those who are not. In this study, the researcher used Quasi Experimental Design using pretest-posttest nonequivalent groups design. There were 80 students taken as sample. Each class consisted of 40 students from class XI IPA 1 as experimental group and class XI IPA 2 as control group. In collecting the data, test was used. The test was given twice to experimental and control groups, as a pretest and posttest. To verify the hypotheses, the data of pretest and posttest were analyzed by using independent sample t-test and paired sample t-test in SPSS program. The findings showed that the p-output from paired sample t-test (sig2-tailed) was 0.000 which was lower than 0.05 and t-value 11.955 was higher than t-table with df=39 (2.0227).  The result of p-output from independent sample t-test was 0.002 which was lower that 0.05 and the t-value 3.250 was higher than t-table with df=78 (1.9908). it means that teching reading hortatory exposition text by using Give One, Get One strategy had significant effect on the students' reading comprehension scores.